2016
DOI: 10.3109/00016489.2016.1143967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cochlear implant surgical technique on post-operative electrode impedance

Abstract: Electrode impedance values were significantly lower in the mCI group than in the CI surgery group at initial activation (5.01 kOhm vs 6.10 kOhm, respectively, F = 13.761, p = 0.000). The differences between the two groups were most prominent for the electrodes located at the basal region of the cochlea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Hamada et al [13] showed no significant differences in electrode impedance between the RW and cochleostomy approaches for 69 pediatric and adult CI users using 4 types of electrodes 1 month after the surgery. Gu et al [12] compared the impact of the modified minimal access CI approach which was improved basing it on RW approach and cochleostomy approaches for 50 pediatric and adult CI users using the same type of electrode and found that electrode impedance values were significantly lower in the minimal access CI group than in the cochleostomy group at initial activation. The minimal access CI group used dexamethasone before they inserted the electrode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamada et al [13] showed no significant differences in electrode impedance between the RW and cochleostomy approaches for 69 pediatric and adult CI users using 4 types of electrodes 1 month after the surgery. Gu et al [12] compared the impact of the modified minimal access CI approach which was improved basing it on RW approach and cochleostomy approaches for 50 pediatric and adult CI users using the same type of electrode and found that electrode impedance values were significantly lower in the minimal access CI group than in the cochleostomy group at initial activation. The minimal access CI group used dexamethasone before they inserted the electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Gu et al [12] showed that the RW approach achieved lower impedance than the cochleostomy approach, whereas Hamada et al [13] held different viewpoints that the RW and cochleostomy approaches provided comparable impacts on electrode impedance. Except for electrode impedance, residual hearing, insertion depth and speech perception were compared between the 2 approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The round window niche is then plugged with fascia or muscle graft after insertion of the electrodes. 43 Plain radiographs are often obtained during and after the operation to evaluate the positioning of the cochlear implant electrodes. 42 Multiplanar HRCT is the preferred imaging modality to evaluate positioning of the individual electrodes in greater detail.…”
Section: Cochlear Implantationmentioning
confidence: 99%
“…Als Schnittstelle zwischen Elektrode und Hörnerv wird der Impedanz ein großer Stellenwert zugesprochen [21,[31][32][33]. Vor allem zur Erkennung von Erkrankungen und Entzündungen des Innenohrs werden er-höhte Werte als Marker angesehen [31,32,34]. Untersuchungen zeigen, dass ein großer Unterschied der Impedanzen zwischen den einzelnen Elektroden eines Implantats signifikant mit einem schlechteren Spachverstehen (SPV) korreliert [21,33].…”
Section: Introductionunclassified